Relationship Between Family Cultural Orientation in Menu Selection and Incidence of Childhood Acute Lymphoblastic Leukemia (LLA) in Surabaya, Indonesia - Indriatie Indriatie; Aida Novitasari; Enung Mardiyana H; Nur Hasanah; Krupa Susan Koshy (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Diseases can be caused by consuming foods that do not have a balanced nutritional value, choosing the wrong diet, or choosing the wrong food menu. Diet is also a risk factor for cancer, such as leukemia. In the outpatient pediatric polyclinic of Dr. Soetomo Hospital Surabaya, leukemia is one of the ten most common diseases. This study aims to analyze the relationship between family culture of menu selection and the incidence of leukemia in children at the Surabaya Halfway House. The population in this study were all mothers or families and children suffering from leukemia waiting for treatment in the hospital and living temporarily in a halfway house on Jl Karang Menjangan, a total of 30 people. This type of research is analytic using a simple linear regression approach/desianalyticallye the dominant factors that influence the culture of food from menu selection with the incidence of leukemia in children. The independent variable in this study is the family culture of menu selection, which is a pattern of behavior that has been carried out by parents or families as a way to meet the needs of food which includes beliefs, knowledge about nutrition, social functions of food, and menu selection, preferences or preferences. The dependent variable is the incidence of Acute Lymphocytic Leukemia (Leukemia/ALL), which is the diagnosis of leukemia based on the medical diagnosis of the patient's status. analyzed by simple linear regression test. Results: the culture of food menu selection (beliefs, knowledge about the food menu, social functions, preferences do not contribute to the incidence of leukeand and mia in children. It is recommended that the culture of food menu selection regarding trust, knowledge, social function, preference is a food menu selection culture that must be maintained because the results obtained mostly have good habits and some are still lacking so it is hoped that the menu selection pattern will become an initial assessment for children diagnosed with cancer to prevent subsequent events.